Nanolithography and patterning techniques in microelectronics - Bucknall, David G. (Woodhead Pub. ; CRC Press, 2005)
Nanolithography and Patterning Techniques in Microelectronics examines the new range of techniques that have made it possible to develop complex patterns at the nanoscale and explores their industrial applications. This book considers ways of forming and modifying surfaces for patterning and provides information on specific patterning techniques such as soft lithography, ion beam patterning, use of nanostencils, photolithography, and inkjet printing. It also discusses prototyping and the manufacture of particular devices. With a distinguished team of contributors, this is an ideal reference for researchers and professionals using advanced polymers in such areas as microelectronics and biomedical devices.